Epidermal growth factor receptor promotes glioma progression by regulating xCT and GluN2B‐containing N‐methyl‐d‐aspartate–sensitive glutamate receptor signaling. Issue 12 (5th November 2018) - Suina, Kentaro; Tsuchihashi, Kenji; Yamasaki, Juntaro; Kamenori, Shohei; Shintani, Subaru; Hirata, Yuki; Okazaki, Shogo; Sampetrean, Oltea; Baba, Eishi; Akashi, Koichi; Mitsuishi, Yoichiro; Takahashi, Fumiyuki; et al.
Abstract : Autocrine and paracrine factors, including glutamate and epidermal growth factor (EGF), are potent inducers of brain tumor cell invasion, a pathological hallmark of malignant gliomas. System xc(–) consists of xCT and CD98hc subunits and functions as a plasma membrane antiporter for the uptake of extracellular cystine in exchange for intracellular glutamate. We previously showed that the EGF receptor (EGFR) interacts with xCT and thereby promotes the activity of system xc(–) in a kinase‐independent manner, resulting in enhanced glutamate release in glioma cells. However, the molecular mechanism underlying EGFR‐mediated glioma progression in a glutamate‐rich microenvironment has remained unclear. Here we show that the GluN2B subunit of the N ‐methyl‐d ‐aspartate–sensitive glutamate receptor (NMDAR) is a substrate of EGFR in glioma cells. In response to EGF stimulation, EGFR phosphorylated the COOH‐terminal domain of GluN2B and thereby enhanced glutamate‐NMDAR signaling and consequent cell migration in EGFR‐overexpressing glioma cells. Treatment with the NMDAR inhibitor MK‐801 or the system xc(–) inhibitor sulfasalazine suppressed EGF‐elicited glioma cell migration. The administration of sulfasalazine and MK‐801 also synergistically suppressed the growth of subcutaneous tumors formed by EGFR‐overexpressing glioma cells. Furthermore, shRNA‐mediated knockdown of xCT and GluN2B cooperatively prolonged the survival of mice injected intracerebrally with such glioma cells. Our findings thus establish a central role for EGFR in the signaling crosstalk between xCT and GluN2B‐containing NMDAR in glioma cells. Abstract : Epidermal growth factor receptor phosphorylated GluN2B and thereby enhanced glutamate‐NMDAR signaling and consequent cell migration in EGFR‐overexpressing glioma cells.